Strategi Komunikasi Pemasaran UMKM "Ayam Geprek Gondes" Dalam Mempertahankan Brand Image - Ari Fatkhur Rizqi; Daukas Falih Arsyad; Raihan Adinoto; Yohanes Ari Kuncoroyakti; Bonar S Panjaitan (JURNAL ILMIAH NUSANTARA, 2025)
This study examines the communication methods used by the MSME "Ayam Geprek Gondes" to maintain its brand image amid fierce competition in the culinary field. With its status as a micro-enterprise developing among students, Ayam Geprek Gondes experiences difficulties in maintaining brand image consistency and customer loyalty. The approach used in this research is qualitative, with a descriptive study method through in-depth interviews and MSME management observations. Research findings reveal that the communication methods applied include utilizing social media, promotions based on customer testimonials, and personal interactions through friendly and consistent service. Additionally, the business owner is active in building relationships with customers and maintaining product quality as a form of wordless communication. This strategy has proven effective in maintaining a positive brand image in consumers' minds. The conclusion of this study highlights the importance of integrated and authentic communication in forming and maintaining brand image, especially for MSMEs that do not have large promotional budgets. Recommendations are provided for MSMEs to continue innovating in conveying brand messages to remain relevant and competitive. This research can serve as a guide for MSME actors in creating effective and economical communication strategies.